The Role of HOS Tjokroaminoto and Kiai Haji Ahmad Dahlan in Soekarno's Journey to Understanding Islam in 1915-1934 - Putri Ambarwati Prayitno; M. Fakhruddin; Kurniawati (Criksetra: Jurnal Pendidikan Sejarah, 2022)
This study aims to find out and also understand Soekarno's Islamic journey which aims to see how far Soekarno's understanding is in understanding himself as a Muslim; see the role of HOS Tjokroaminoto and Kiai Haji Ahmad Dahlan in influencing Soekarno regarding modernist Islamic thought and see the influence of HOS Tjokroaminoto and Kiai Haji Ahmad Dahlan in influencing Soekarno's thoughts on Islam. The method used is the historical narrative method. The results of this study are able to explain the background and influence of these two figures on Soekarno in understanding his religion. Can know and understand Soekarno's journey to know and explore Islam. Based on the results of this study, it can be concluded that along Soekarno's journey to know Islam there was an important role of HOS Tjokroaminoto and K.H Ahmad Dahlan in giving influence, understanding and Islamic thought to Soekarno. Therefore, the purpose of these figures in proclaiming modern Islamic thoughts is solely for the benefit of Muslims so that they are always ready to face future challenges.